Body image and self perception among African American women aged 18-30 - West, Shelia F. (Kansas State University, 2012)
The purpose of this study was to explore how African American women think and feel about their bodies. Specifically, this study examined how Black women define beauty by means of variables such as body shape, skin complexion, and hair texture; whether African American women ages 18-30 compared themselves to media images; and if so, did comparison to these media images impact African American women’s body satisfaction. In addition, this study explored if African American women felt pressure to adopt beauty standards attributed to the dominant culture, as well as the role of racial identity in forming beauty standards and social comparison behavior. Twelve African American women were interviewed and findings of this exploratory research illustrated that the Black community has different standards than the traditional beauty standards of the U.S. Even though interviewees articulated standards of beauty for women in the Black community, there was a lack of uniformity in how these women felt about their own attractiveness: some identified with the Black beauty standards, while others did not. In addition, opinions varied regarding Black women’s engagement in social comparison behavior and whether it was related to racial identity or body satisfaction. Limitations of study included: how Black women define social comparison behavior and racial identity, self-identification of participants, and the lack of Caucasian women included in this study. However, this research still provided rich data exploring Black women’s perceptions of beauty among other issues within the Black community. Future research is required to better understand influences shaping standards of beauty within this subculture of the United States and recommendations are provided in the last chapter.
Keywords: Body image; Body satisfaction; African American women; Social comparison theory; Beauty; Racial identity; African American Studies (0296); Social Psychology (0451); Women's Studies (0453)